When ethnographic work turns into distant screen visits: A note on flexible inflexibility during the COVID-19 pandemic. (September 2022) - Sandberg, Helena; Sundin, Ebba; Sjöberg, Ulrika
This colloquium shares experiences from doing ethnographic fieldwork with young children and the challenges that followed due to the COVID-19 pandemic. The project DIGIKIDS Sweden has its focus on very young children (birth to three years) and their engagement with digital media technologies in their homes. The pandemic put the project on hold, but in the families where the fieldwork had already started, the authors decided to change the methods of data collection. Digital screen visits were introduced and, at first, this seemed to be flexible, and they adjusted to the new environment. At the same time, this flexibility also became an inflexible experience due to the use of technology.